Gender, Embodiment and Fluidity in Organization and Management - McMurray, Robert, 1972-; Linstead, Alison, 1971- (London : Routledge, 2019)
This third volume in the RoutledgeFocus on Women Writers in Organization Studies serieschallenges us to think again about the implications of gender, embodiment and fluidity for organizing and managing. The themes of this book disrupt our understanding of dualisms between sex (men and women), gender (masculinity and femininity) and mind / body, and in so doing analyze the ways in which dominant power relations constitute heteronormativity throughout organizational history, thereby reinforcing mainstream management research and teaching. By centring the work of women writers, this book gives recognition to their thinking and praxis; each writer making political inroads into changing the lived experiences of those who have suffered discrimination, exclusion and marginalization as they consider the ways in which organizational knowledge has tended to privilege rather than problematize masculinity, fixity, control, normativity, violence and discrimination. The themes and authors (Acker, de Beauvoir, Halberstam, Kosofsky Sedgwick, Kristeva, Yourcenar) covered in this book are important precisely because they are not generally encountered in mainstream writing on management and organization studies. They are significant to the study and analysis of organizations because they demonstrate how our understanding of managing and organizing can be transformed when other voices/bodies/genders write on what it is work, live, lead and relate to self and others. All the writers turn to the ways in which individuals matter organizationally, acknowledging that lived experiences are a source of political and ethical practice. Each Woman Writer is introduced and analyzed by experts in organization studies. Further reading and accessible resources are also identified for those interested in knowing more. This book will be relevant to students, researchers and practitioners with an interest in business and management, organizational studies, critical management studies, gender studies and sociology. Like all the books in this series, it will also be ofinterest to anyone who wants to see, think and act differently.
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Organizational Behavior; Organizational sociology; Sex role; Feminism; Queer theory